Karakteristik Dan Petrogenesa Batuan Beku Granit Di Daerah Sibayu, Kecamatan Balaesang, Kabupaten Donggala, Provinsi Sulawesi Tengah - Wahdaniah Mukhtar; Nurhikmah Supardi (Jurnal Geomine, 2022)
The tectonic history of Sulawesi is closely related to the activities of the three major world plates that surround it. This results in the complexity of geological conditions on the island of Sulawesi, including the diversity of rock types. One of the most common types of rock is igneous granite, which is widespread in the Sibayu area, Donggala Regency, Central Sulawesi Province. This study aims to determine the characteristics and petrogenesis of igneous granite using megascopic and microscopic or petrographic observation methods. The results showed that the rock has a megascopic appearance in the form of a grayish-white fresh color and a brownish weathered color, a holocrystalline texture, a massive structure, and a mineral composition consisting of orthoclase, amphibole, and quartz. Its microscopic appearance shows a brownish-transparent color on parallel nikol, on brown cross-linked nikol, light gray to dark gray, mineral size 0.15-0.05 mm, the average mineral composition is orthoclase (41.25% ), quartz (43.75%), biotite (11.25%) and plagioclase (3.75%). Based on these data, it can be concluded that the rocks are Late Miocene to Late Pliocene, which proves that the Palu-Koro fault was still active during the Late Miocene to Late Pliocene. The presence of biotite in granitic rocks characterizes S-Type granite which is formed deep below the earth's surface which is characterized by euhedral-subhedral forms.